Implementasi Digital Marketing Produk Funsit Id Melalui Media Sosial Instagram Dalam Meningkatkan Minat Beli Followers Di Kota Makassar - Maharani Nur Annisa , Siti; Ahdan, Ahdan; Muttaqin , Andi (UNIVERSITAS MUSLIM INDONESIA, 2022)
This study aims to: determine the implementation of digital marketing for Funsit Id followers, and find out how Funsit Id increases buying interest in Funsit Id account followers. The method used in this research is descriptive qualitative. Using Interview, Observation, and Documentation Methods. This research lasted for approximately one month located at Jalan Telkomas Raya no.1. The research informants are the Funsit Id owner and also followers who are followers of the Funsit Id instagram account. The results of this study indicate that the implementation of Digital Marketing for Funsit Id Products through Instagram Social Media in Increasing Interest in Buying Followers in Makassar City is using Instagram social media by utilizing various available features such as reels, instastory, as well as using brandambassador services and making give away events. And the diversity of product menu innovations presented by Funsit Id makes followers spoil their eyes through postings on the Funsit Id Instagram account so that they can increase buying interest.